PERENCANAAN BANGUNAN MCK UNTUK KEBUTUHAN MASYARAKAT DI KAMPUNG SETU TONGGOH - Rizky Aulia Rahmah; Rulhendri Rulhendri (JPMUJ, 2023)
MCK is one of the public facilities which are usually shared by several families to bathe, wash and defecate in a settlement which can be judges as a location with a fairly dense population and low economic. One of villages in Bogor Regency still uses MCK because it doesn’t have a private toilet in each house. The number of people who use the MCK is 25 people. The MCK used by the community is still not suitable for use, so that they are more flexible and comfortable when used, we plan to repair the MCK. For the sake of creating a suitable bathroom for use and realizing MCK that there are no proper repair facilities. This research contains that the availability of a new MCK design can help the community rebuild the MCK. Hopefully this MCK planning can be realized because with proper planning it can minimize bathroom problems faced by the community.